KONSEP PENDIDIKAN UNGGUL DALAM AL-QUR’AN (KAJIAN TEMATIS SURAT LUQMAN) - Taufikurrahman Taufikurrahman (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2016)
Al-Qur’an contains many valuable pointers on educational matters. Surah Luqmān, the 31st surah in al-Qur’an, is one of several important repositories of those pointers. This article tries to scrutinize the concept of Excellent Education in Surah Luqmān by focusing on two main points, namely the aim of education and the curriculum of childhood education. The study reveals that excellent education in al-Qur’an directs people to know their selves well and to perform their true functions in life. The concept of excellent education in al-Qur’an is formulated in an integrated and all-inclusive curriculum aiming at refinement of all potentials of human intteligence, namely spiritual intteligence, emotional intelligence, and cognitive-rational intelligence. This curriculum emphasizes five central matters in human life, namely tauhid, acts of worship, ethic, mentality, and management of life. When the children are well educated on these five central matters, they will totally improve in order to find happiness in this wordly life and in the hereafter.